Factors affecting gains - Bell, F.W.; Smith, E.F.; Smith, W.H. (Kansas Agricultural Experiment Station, 2012)
Cattle in the same feedlot differ considerably in their rate of gain. These differences in ability to gain can be explained only by difference in characteristics of individual animals, since all are under the same conditions of feeding and care. In this study, we are trying to determine what differences in thin cattle are reliable indications of gaining ability. A record of several characteristics is made of each animal at the beginning of the feeding trials.
Keywords: Beef; Gain; Steers